Збірник статей здобувачів вищої освіти другого (магістерського) рівня Навчально-наукового інституту фінансів, банківської справи Університету ДФС України : у 6-ти ч. Ч. 5. - ННІ фінансів, банківської справи; Institute of Finance, Banking (Ірпінь, 2019)
У збірнику опубліковано статті здобувачів вищої освіти другого (магістерського) рівня. Видання призначене для молодих вчених, аспірантів, здобувачів вищої освіти. The collection publishes articles by students of the second (master's) level of higher education. The publication is intended for young scientists, post-graduate students, students of higher education.
A collection of articles by students of the second higher education (master's) level of the Educational and Scientific Institute of Finance, Banking of the University of the SFS of Ukraine: in 6 h. Ch. 5.
Keywords: банківська справа, фінансові інститути, фінансовий моніторинг, державне регулювання діяльності банківських установ; banking, financial institutions, financial monitoring, state regulation of banking institutions